A divulgação científica presente na revista Ciência Hoje das Crianças: diálogos sobre o que é e quem faz ciência. - SANTOS, Stella Chystine Câmara dos (2021)
The present work mainly aimed to investigate Science Popularization (SP) in the magazine Ciência Hoje das Crianças (CHC), focusing on the representations of Science and scientists. This documental research has a qualitative approach, whose corpus was assembled from a temporal dimension stablished between March 2016 to June 2019. Analyses were carried out based from the referential on content analysis, from which ten categories emerged: individualist-elitist; gender and position; representativity; origin of scientists; text authorship; making Science; Science (de)contextualization; ludic dimension; combative dimension; and multimediatic dimension. Regarding representations of scientists during our analyses, CHC showed a controversial vision as it still brings individualistic examples, which may contribute to a vision of Science made exclusively by genius men. On the other hand, female scientists were also represented at times, a very important result as fights for more gender equity in the scientific field have been raised. CHC predominantly displayed examples of scientists originated from Europe or descended from such continent, which may lead to a revalidation of stereotypes on Science epistemologies. In relation to the representations of Science found in the magazine, a duality is present as Science is sometimes shown as tough, rigid, built upon one unique scientific method, and as a manual to be followed, prioritizing the Natural Sciences. Nonetheless, many aspects were found to display a more diverse, and complex Science made by a plurality of actors share information to each other. Such duality is found in our results, which may indicate a disparity between making Science and the real scientists, and the form this goes in SP materials, which may lead people to misunderstanding it. Regarding the characteristics of SP in CHC magazine, notorious elements could be found which aimed to attract the attention of readers, thus making the magazine more ludic. This way, CHC efforts, although tentatively, combating fake news about Science that spread in society. Furthermore, we found relevant indications of more dynamicity, deepening, and dialogicity as important characteristics when relating both mediatic ways, despite the magazine not having fully explored the potentialities of it. Based on our discussions, we point out to a reorientation of how SP materials are made, especially the representations of Science and scientists, to rethink the way Science is and is made so that diversity and plurality are taken in consideration, as well as to the new social and technological demands present in our current society, in order to make such materials can help populations build knowledge.